Saliva cortisol in relation to aircraft noise exposure: pooled-analysis results from seven European countries - Clémence Baudin; Marie Lefèvre; Jenny Selander; Wolfgang Babisch; Ennio Cadum; Marie-Christine Carlier; Patricia Champelovier; Konstantina Dimakopoulou; Danny Huithuijs; Jacques Lambert; Bernard Laumon; Göran Pershagen; et al. (BMC, 2019)
Abstract Background Many studies have demonstrated adverse effects of exposure to aircraft noise on health. Possible biological pathways for these effects include hormonal disturbances. Few studies deal with aircraft noise effects on saliva cortisol in adults, and results are inconsistent. Objective We aimed to assess the effects of aircraft noise exposure on saliva cortisol levels and its variation in people living near airports. Methods This study focused on the 1300 residents included in the HYENA and DEBATS cross-sectional studies, with complete information on cortisol sampling. All the participants followed a similar procedure aiming to collect both a morning and an evening saliva cortisol samples. Socioeconomic and lifestyle information were obtained during a face-to-face interview. Outdoor aircraft noise exposure was estimated for each participant's home address. Associations between aircraft noise exposure and cortisol outcomes were investigated a priori for male and female separately, using linear regression models adjusted for relevant confounders. Different approaches were used to characterize cortisol levels, such as morning and evening cortisol concentrations and the absolute and relative variations between morning and evening levels. Results Statistically significant increases of evening cortisol levels were shown in women with a 10-dB(A) increase in aircraft noise exposure in terms of LAeq, 16h (exp(β) = 1.08; CI95% = 1.00-1.16), Lden (exp(β) = 1.09; CI95% = 1.01-1.18), Lnight (exp(β) = 1.11; CI95% = 1.02-1.20). A statistically significant association was also found in women between a 10-dB(A) increase in terms of Lnight and the absolute variation per hour (exp(β) = 0.90; CI95% = 0.80-1.00). Statistically significant decreases in relative variation per hour were also evidenced in women, with stronger effects with the Lnight (exp(β) = 0.89; CI95% = 0.83-0.96) than with other noise indicators. The morning cortisol levels were unchanged whatever noise exposure indicator considered. There was no statistically significant association between aircraft noise exposure and cortisol outcomes in men. Conclusions The results of the present study show statistically significant associations between aircraft noise exposure and evening cortisol levels and related flattening in the (absolute and relative) variations per hour in women. Further biological research is needed to deepen knowledge of the pathway between noise exposure and disturbed hormonal regulation, and specially the difference in effects between genders.